Knowledge and Preventive Action of Pulmonary Tuberculosis Transmission in Household Contacts - Saflin Agustina; Chatarina Umbul Wahjuni (Universitas Airlangga, 2017)
Tuberculosis is an infectious disease directly caused by Mycobacterium tuberculosis. Family involvement for its prevention need to be taken into account includes knowledge, attitudes and practice.  The purpose of this study was to analyze the differences of the prevention behavior of the disease in household contact families in the working area of Puskesmas Rangkah, Pacar Keling and Gading at Surabaya 2015.  This research was case control study uses a sample of 25 cases and 25 control samples. Collecting data using questionnaires to obtain information about the variables: the prevention of the disease transmission, socio-economic status, gender, knowledge and attitudes.  The results showed that the majority of respondents have a socio-economic status in the low category (72 %), female (58 %), have a good knowledge (78 %), a good attitude (72 %), and good transmission prevention of pulmonary TB (56 %). Chi square test showed that there is a gender difference (p = 0.010). Wilxocon Mann Whitney test shows that no differences in socioeconomic status (p = 0.533), attitude ( p = 0.212 ) and there are differences in knowledge (p = 0.018) and action (p = 0.000) prevention of transmission of the disease in the household contacts. It can be concluded that there is a difference in behavior includes knowledge and preventive measures of pulmonary TB transmission in the household contacts. Suggest the need for cooperation and intervention from a health personnel to family and patient as well as the strong motivation of the people against infection-prevention measures of pulmonary TB.     Keywords: family, knowledge, attitude, precaution of Pulmonary Tuberculosis infection